Weaponising #Fakenews on Twitter: Generating Flak or Critiquing the Status Quo in the Trump Era? - Berry, Alan R.; Rosenbaum, Judith E.; Corey, Amy M. (Javnost-The Public, 2023)
The phrase “fake news” has become a household term in recent years, a feat that can in large part be attributed to its popularity during the Trump presidency. Utilising social media platforms such as Twitter, the former president and his followers used the hashtag #FakeNews to attack politicians, civic leaders, as well as media organisations with the goal of “draining the swamp.” This combination of anti-establishment rhetoric with the status quo embodied by the Office of the President raises questions about whether the rhetoric associated with the hashtag is genuine, citizen-driven critique or is in fact a form of flak, a critique of the news media produced by powerful organisations and governmental entities, as defined by the Propaganda Model (PM). This study offers an empirical analysis through a qualitative examination of social media posts using #FakeNews in conjunction with posts about immigration issues 2016–2020. Findings show that both pro-Trump and anti-Trump Twitter users utilise #FakeNews to attack the other side, obfuscate the issue, or double down on their stance, indicating that flak is systemically generated to distract citizens from effectively challenging the status quo.